Effect of various photoperiods towards lollo bionda growth using IoT based lighting control for indoor hydroponic farming system. Issue 1 (1st December 2022) - Shafie, A M M; Azlan, A; Sariman, M Z; Mustafa, M M B; Sulaiman, H; Fairuz, K
Abstract: Sustainable agriculture is actively developed to ensure food security which is a major threat to the world population in 2050 as projected by the Food and Agriculture Organization (FAO). The increasingly limited agricultural land nowadays makes indoor farming the best. Indoor farming is the method of growing crops in vertically stacked layers by implementing hydroponic and artificial light. Light Emitting Diodes (LEDs) have been widely used to mimic sunlight for plant growth. However, every plant growth depends on the difference optimal value of light quality (light spectrums) and quantity (photoperiod). This study investigates the effect of light exposure on Lollo Bionda growth and determines which growing environment will provide optimum results in growing Lollo Bionda. This study conducted four types of experiments with different photoperiod treatments, namely T1 (no light exposure), T2 (24 hours), T3 (18 hours) and T4 (12 hours), with six replicates. The results show significant differences between each treatment mean. T2 provides the most significant result for all parameters compared to other treatments. In summary, light exposure helps in the productivity consistency in terms of weight, height and average leaf size of Lollo Bionda. This finding can be beneficial to the small-medium size entrepreneur.